Application of small punch test to estimate mechanical behaviour of SUS304 austenitic stainless steel - Doan, The Yen; Pham, Hang Thi (Vietnam Journal of Mechanics, 2024)
The small punch test with an application of a relatively small specimen has recently become a reliable material mechanics testing method. In this study, the small punch test is set up based on the conventional mechanical testing machine for SUS304 stainless steel to evaluate the mechanical properties of SUS304 steel at different displacement rates of the punch in quasi-static loading condition in the case of with and without heat treatment. Although heat treatment has an insignificant effect on the microstructure and hardness of the material, the mechanical properties of the material in the small punch test are greatly reduced after heat treatment. Both cases with and without heat treatment have a similar tendency for the rate - sensitivity of the applied force - displacement curve. A higher value of force is applied to obtain the same value of displacement at a low displacement rate in the stable plastic deformation zone. Meanwhile, the maximum value of applied force is higher at a higher displacement rate in the stage that initiation of crack might appear. In the examined range of displacement rate, a positive rate - sensitivity of displacement at the maximum force. Therefore, a correlation between equivalent fracture strain and fracture toughness of the material can be achieved.